Classification of Methods of Studies with the Use of Mechanism of Memberwise Disjunctions - Roman Zіn’ko; Oksana Bіlyk; Uliana Khanas (Pedagogical Discourse, 2014)
The problem of classification of methods of studies remains actual, as enables to analyse potential of every method and set the ways of its perfection, subsequent development and introduction. Plenty of going near classification of methods of studies is explained complication of research object and seriousness of tasks, put society before modern professional school. Using the mechanism of memberwise disjunctions is offered for classification of methods of studies which will allow taking into account more wide row of signs of different methods of studies. Systematization of the basic known methods of studies is conducted for this purpose. This systematization of methods contains the different plurals of descriptions which describe them the proper categories and named objects. Objects determine ponderability of description and can take a place in a linear row in obedience to growth or slump of size of ponderability of description. Farther built table which represents connection between the area of localization of descriptions and subject variables. From the general volume of signs in a dominant plural determine signs, which can be characterized after a criterion, for example, of level of activity of student. A predicate which describes classification copulas between the methods of studies will have a characteristic kind. If to form a transition function from a subject domain to the local areas of classification signs after other criterion, for example, on the dominant method of passing to maintenance, a predicate will mutate. Visualization of the offered classification by counts keeps informing at the report of multidimensional information to the comfortable for human perception kind, simplifies perception of such classification and accents attention on its features. The new method of classification of methods of studies with the use of mechanism of memberwise disjunctions is offered will allow to take into account more wide row of signs of different methods of studies.